2021
DOI: 10.1002/aelm.202100277
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances towards Ocean Energy Harvesting and Self‐Powered Applications Based on Triboelectric Nanogenerators

Abstract: Ocean contain abundant clean energies including tidal and wave, but such energies are known for low frequency and large excitation amplitude, posing considerable challenges for high‐efficiency energy conversion. As an emerging technology, triboelectric nanogenerators (TENGs) have been widely used in energy harvesting and novel sensor design due to their high sensitivity and flexible structure. Meanwhile, they show great advantages in the low‐frequency environment (<5 Hz), and display great potential for deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 227 publications
(347 reference statements)
0
25
0
Order By: Relevance
“…The electrification of water droplets after sliding or rolling on hydrophobic surfaces has increasing interest for its applications in energy harvesting devices. A particular case corresponds to the slide/roll of water drops on hydrophobic polymers, poly­(tetrafluoroethylene) (PTFE) being the paradigmatic polymer for observing this phenomenon. The situation to describe is the following: water drops are delivered, one after another, on the tilted (almost vertical) surface of a hydrophobic polymer (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrification of water droplets after sliding or rolling on hydrophobic surfaces has increasing interest for its applications in energy harvesting devices. A particular case corresponds to the slide/roll of water drops on hydrophobic polymers, poly­(tetrafluoroethylene) (PTFE) being the paradigmatic polymer for observing this phenomenon. The situation to describe is the following: water drops are delivered, one after another, on the tilted (almost vertical) surface of a hydrophobic polymer (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…We propose here that both phenomena, the LPCE generated during drop sliding/rolling and the establishment of ξ-potential at the polymer–solution interface, may have the same origin: the acid–base equilibrium on the polymer surface. The subject is still under debate, and although it is commonly observed that surfaces of several hydrophobic polymers in contact with neutral water (pH = 7) acquire a negative charge, this is not always exclusively explained or interpreted by assuming OH – adsorption but by asymmetries in the H-bond at the surface or electron transfer processes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Most recently, as oceans contain a huge amount of energy and are completely predictable and reliable, the generation of electricity based on oceans is becoming very popular. Electricity generation from oceanic energies can be either on large-scales [5], such as wave activated bodies [6], point absorbers [7,8], oscillating water columns [9], and overtopping [10] concepts, for cities and industries, or on small-scales using piezoelectric [11], electrostatics [12], electromagnetics [13], and triboelectric [14] devices for powering low power devices, such as the internet of underwater things, sensors, and other monitoring devices in oceans [15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the devices shown in this review work with TENG or hybrid systems, TENG and EMH (electromagnetic harvesting). Shen et al [ 17 ] presented recent advances towards ocean energy harvesting and self-powered applications based on triboelectric nanogenerators and the study of different materials and configurations. In this review, it was stated that at present, the most employed hybrid generator is the EMG (electromagnetic generator)-TENG, as EMGs increase the current of hybrid generators.…”
Section: Introductionmentioning
confidence: 99%